2019
DOI: 10.1021/acs.est.9b01191
|View full text |Cite
|
Sign up to set email alerts
|

Field and Laboratory Studies Linking Hydrologic, Geochemical, and Microbiological Processes and Enhanced Denitrification during Infiltration for Managed Recharge

Abstract: We present linked field and laboratory studies investigating controls on enhanced nitrate processing during infiltration for managed aquifer recharge. We examine how carbon-rich permeable reactive barriers (PRBs) made of woodchips or biochar, placed in the path of infiltrating water, stimulate microbial denitrification. In field studies with infiltration of 0.2–0.3 m/day and initial nitrate concentrations of [NO3-N] = 20–28 mg/L, we observed that woodchips promoted 37 ± 6.6% nitrate removal (primarily via deni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 55 publications
3
28
0
Order By: Relevance
“…Similarly, in situ amendments for infiltration basins have been proposed, including addition of carbon sources (e.g., wood chips) to create a horizontal permeable reactive barrier and promote denitrifying conditions. These studies focus on nitrate removal from recharge water during infiltration and associated shifts in microbial community structure. While nitrate is a primary contaminant, preventing nitrate from reaching deeper groundwater supplies can also minimize the potential for oxidation of reduced immobile geogenic contaminant phases (e.g., arsenian pyrite, uraninite) limiting mobilization potential along the flow path.…”
Section: Water Quality Considerations For the Future Of Marmentioning
confidence: 99%
“…Similarly, in situ amendments for infiltration basins have been proposed, including addition of carbon sources (e.g., wood chips) to create a horizontal permeable reactive barrier and promote denitrifying conditions. These studies focus on nitrate removal from recharge water during infiltration and associated shifts in microbial community structure. While nitrate is a primary contaminant, preventing nitrate from reaching deeper groundwater supplies can also minimize the potential for oxidation of reduced immobile geogenic contaminant phases (e.g., arsenian pyrite, uraninite) limiting mobilization potential along the flow path.…”
Section: Water Quality Considerations For the Future Of Marmentioning
confidence: 99%
“…Nitrate leaching and N transformation processes have been studied in more detail in traditional MAR systems such as storm water or treated wastewater infiltration basins (Abiye et al, 2009;Ben Moshe et al, 2020;Goren et al, 2014;Gorski et al, 2019;Schmidt et al, 2011). Depending on the infiltration rate of the native soil, Schmidt et al (2011) observed a 30-60% removal of NO 3 − in agricultural storm runoff recharged in a 3-ha infiltration basin.…”
Section: Core Ideasmentioning
confidence: 99%
“…Although traditional MAR systems have similar end goals to Ag‐MAR, major hydrologic differences exist between these systems. In contrast with MAR infiltration basins, which often maintain a constant head of several meters for several weeks, creating a thick saturated layer beneath the basin surface (Gorski et al., 2019; Schmidt et al., 2011), previous Ag‐MAR projects often had smaller heads (10–50 cm). In addition, on agricultural fields planted with perennial crops, the water was applied in short‐lived pulses on high‐infiltration‐capacity soils to avoid waterlogged conditions that could potentially harm the crops.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring soil physical-biogeochemical processes during MAR has been extensively studied (Danfoura & Gurdak, 2016;Ganot et al, 2018;Gorski et al, 2019;Greskowiak et al, 2005;McNab et al, 2009;Rodríguez-Escales et al, 2020;Schmidt et al, 2011;Vandenbohede et al, 2013); however, since Ag-MAR is a relatively new technique in the MAR toolbox, to date only a few studies have monitored these processes in actual agricultural fields during Ag-MAR (Bachand et al, 2014(Bachand et al, , 2016(Bachand et al, , 2019Dahlke et al, 2018;Dokoozlian et al, 1987). Most Ag-MAR studies have focused on developing soil suitability guidelines (O'Geen et al, 2015), regionalscale aquifer storage estimations (Scanlon et al, 2016), water availability analysis (Kocis & Dahlke, 2017), hydro-economic analysis (Gailey et al, 2019), and benefits evaluation using numerical modeling (Kourakos et al, 2019;Niswonger et al, 2017).…”
Section: Core Ideasmentioning
confidence: 99%